PATHOGENETIC TREATMENT OF ENZYMATIC PARAPANCREATITIS - Dmitriy V. Kulikov; Andrey Y. Korolkov; Victor P. Morozov; Alexey A. Vaganov (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2019)
Relevance. The most severe component of acute destructive pancreatitis (ADP) is enzymatic parapancreatitis (EPP). Pathogenetic treatment methods are limited.The objective was to evaluate the effectiveness of different treatment methods.Material and methods. Group 1 included 86 patients with ADP, enzymatic peritonitis (EP), EPP; 44 patients with EPP of them were performed LD of the retroperitoneal tissue. Group 2 included 120 patients with EPP without EP, 48 – with PPD (percutaneous drainage of parapancreatic tissue).Results. Mortality rate in patients with hemorrhagic EPP with LD was 16 %, without LD – 37 %, in patients with serous EPP with LD – 15 %, without LD –15 %. Mortality rate in patients with EPP without EP and with PPD was 6.2 %, without PPD – 8.3 %Conclusion. LD and PPD should have been applied on the basis of the variant of EPP.